More sentinel lymph node biopsies for thin melanomas after transition to AJCC 8th edition do not increase positivity rate: A Danish population‐based study of 7148 patients. Issue 3 (21st October 2021) - Weitemeyer, Marie B.; Helvind, Neel M.; Brinck, Anne M.; Hölmich, Lisbet R.; Chakera, Annette H.
Abstract: Background: We evaluated the outcome of sentinel lymph node biopsies (SLNB) in patients with thin melanoma before and after the implementation of AJCC 8th edition (AJCC8) and identified predictors of positive sentinel lymph nodes (+SLN). Methods: Patients diagnosed with T1 melanomas (Breslow thickness ≤1 mm) during 2016–2017 as per AJCC 7th edition (AJCC7) ( n  = 3414) and 2018–2019 as per AJCC8 ( n  = 3734) were identified in the Danish Melanoma Database. Results: More SLNBs were performed in the AJCC8 cohort compared to the AJCC7 (22.2% vs. 16.2%, p  < 0.001), with no significant difference in +SLN rates (4.7% vs. 6.7%, p  = 0.118). In the AJCC7 + SLN subgroup, no melanomas were ulcerated, 94.6% had mitotic rate (MR) ≥ 1, 67.6% were ≥0.8 mm and 32.4% would be T1a according to AJCC8. In the AJCC8 + SLN subgroup, 10.3% were ulcerated, 74.4% had MR≥ 1, 97.4% were ≥0.8 mm and 23.1% would be T1a according to AJCC7. On multivariable analysis younger age and MR ≥ 1 were significant predictors of +SLN. Conclusion: More SLNBs were performed in T1 melanomas after transition to AJCC8 without an increase in +SLN rate. None of the AJCC8 T1b criteria were significant predictors of +SLN. We suggest that mitosis and younger age should be considered as indications for SLNB in thin melanoma.